The Effect Of The Project-Based Learning Model On Students' Problem-Solving Skills: A Literature Review - Baiq Anisya Nelahi Purnadya; Maria Anastasia Da Lopez (Indonesian Journal of Applied Science and Technology, 2023)
Problem-solving ability is one of the essential competencies that students should develop in physics learning. However, many students still demonstrate low problem-solving skills, indicating the need for learning models that actively engage them in critical and systematic thinking. Project-Based Learning is considered one of the instructional models capable of addressing this need. This study aimed to analyze the effect of Project-Based Learning on students' problem-solving ability in physics through a literature review. The study employed a literature review method by analyzing ten research articles published between 2014 and 2023, which were selected from Google Scholar based on predetermined inclusion criteria. The findings indicate that all reviewed studies reported a positive effect of PjBL on students' problem-solving ability. The improvement was reflected in significant statistical test results, higher normalized gain (N-Gain) scores, and better average learning outcomes in experimental groups than in control groups. These findings suggest that PjBL facilitates students in identifying problems, connecting physics concepts, developing solution strategies, and evaluating solutions through project-based learning activities. Therefore, Project-Based Learning can be considered an effective instructional model for improving students' problem-solving ability in physics learning.